Prioritizing marine water pollution factors for marine transportation using the analytical hierarchy process (AHP): A case study of Port Klang - Izyan Hakimah Kamar Supardi; Mohamad Abdullah, Nazirah (Recent Trends in Civil Engineering and Built Environment, 2025)
Marine transportation is essential to global trade but significantly contributes to marine water pollution, particularly in Port Klang. This study uses the Analytic Hierarchy Process (AHP) to prioritize factors affecting marine pollution, such as chemical pollution, biological pollution, physical disturbance, antifouling paints, waste disposal, and regulation. AHP reveals chemical pollution and physical disturbances as the most critical contributors, followed by waste disposal. The findings provide policymakers with valuable insights for resource allocation and pollution mitigation, showcasing AHP's effectiveness in addressing marine pollution and promoting sustainable maritime practices.